Fine-tuning of radiative properties by “mild” substituents: searching for a perfectly soft chromophore - Senge, Mathias (My University, 2024)
Controlling spectral properties to achieve desired characteristics is an attractive goal in application- oriented research, e.g., in the design of fluorescence sensors. ‘‘Soft’’ chromophores, molecules with strong spectral responses to internal or external perturbations are good candidates for such studies. In this work, absorption, fluorescence, and magnetic circular dichroism (MCD) spectra were obtained for a series of porphyrins, substituted at the meso-positions with n-hexyl groups. As the number of substituents increases from 1 to 4, significant changes are observed. The intensity of the S0 –S 1 transition (Qx) in the 0–0 region strongly decreases in mono-substituted porphyrin, but upon additional substitutions it increases to values larger than in the parent, unsubstituted molecule. Such behavior can be explained, using the perimeter model, by changes in the energy splittings between the two highest (HOMO) and two lowest (LUMO) frontier molecular orbitals. Single substitution makes porphyrin a nearly perfect soft chromophore, but upon introduction of a larger number of n-hexyl groups it is transformed into a hard one. DFT simulations incorrectly predict a continuous transition from a soft to hard chromophore, because the calculated ordering of two HOMO orbitals is opposite to that obtained by experiment. On the other hand, for those porphyrins that can be classified as hard chromophores, the calculations nicely reproduce contributions of Franck–Condon and Herzberg–Teller terms to absorption and fluorescence spectra.